CO laser resurfacing for burn and traumatic scars of the hand and upper extremity - Cameron Cox; Patrick Bettiol; Audrey Le; Brendan J MacKay; John Griswold; Desirae McKee (SAGE Publishing, 2022)
Background Scar formation is a normal part of the proliferative phase in wound healing where collagen is remodelled to better approximate normal skin. When collagen is not effectively redistributed, excessive scarring may occur. Recently, CO 2 laser has emerged as an adjunct in improving scar quality via remodelling and redistribution of dermal collagen fibres. Due to the paucity of literature related to its use in the hands and upper extremities, we created a study to examine its effects on hypertrophic scars focused on the hands and upper extremities. Methods Patients treated with CO 2 laser for hypertrophic scars of the hand and upper extremity were included. The Vancouver Scar Scale (VSS) and Patient and Observer Scar Assessment Scale (POSAS) were used to assess the progression of scar quality. Unpaired t-tests were performed to determine statistical difference between pre- and post-treatment scores on each scale. Pearson correlation coefficients were used to understand the relationship between number of treatments and scar quality. Results Of the 90 patients enrolled, 54 patients completed serial scar assessment forms. All patient and observer-reported POSAS domains showed improvement ( P  < 0.05) apart from Itching . All VSS domains showed improvement ( P  < 0.05). There was moderate correlation between overall patient-reported opinion of scar quality and Discoloration , Stiffness and Thickness , and strong correlation between overall patient opinion and Irregularity (r = 0.715). All observer-reported domains were strongly correlated (r = 7.56-8.74) with overall observer opinion of scar quality. Conclusion The results of this study may further substantiate CO 2 laser as a treatment modality for excessive scarring in a variety of surgical subspecialties. Lay Summary Complex trauma and burns that impact the skin sometimes result in abnormal healing of the skin called, "hypertrophic scarring". In our study we assessed how using focused CO 2 laser therapy impacts patients and health care provider assessment of wound progression. Our results were based upon patient reported and healthcare provider observations based upon two standardized forms the Vancouver Scar Scale (VSS) and the Patient and Observer Scar Assessment Scale (POSAS). What we found is that after CO 2 Laser Therapy, our 64 patients with 77 treated scars received on average almost 3 treatments and these treatments helped them with physical function and improved aesthetic appearance of their scars. The health care providers also found that the treatments improved functional and aesthetic end points. Overall, our study helps substantiate the body of evidence that using CO 2 laser therapy improves aesthetics and function of hypertrophic scars in the upper extremity.